Internet of things in the healthcare industry - Udmale S.S.; Pandey A.K.; Singh R.S.; Singh S.K. (My University, 2025)
Extensive research has helped to make the extraordinary progress in multiple technologies and as an effect it has strengthened the existing medical services. Specifically, the introduction of the Internet of things (IoT) in the healthcare industry has shown promising results by connecting the various medical resources for efficient utilization. Thus, an IoT-based healthcare system has been broadly accepted for trustworthy, useful, and smart healthcare services. This chapter aims to provide an overview of IoT and its importance in the healthcare industry. The business opportunity and quality of services requirements for the design and development of IoT-based systems are discussed. © 2021 Elsevier Inc. All rights reserved.